An analysis of cash waqf participation among young intellectuals - Osman, Amirul faiz; Mohammed, Mustafa Omar; Amin, Hanudin (Universiti Sains Islam Malaysia (USIM), 2014)
Considering the importance of cash waqf in developing waqf institutions and enhances the social economic of ummah. Yet, the literature that contributes to a social psychological understanding of the factors that underlie an individual’s decision to donate to cash waqf has been extremely inadequate. This study therefore is aimed at examining the determinants of donor (waqif) intention to participate in giving cash waqf in the context of muslim in Malaysia particularly amongst young intellectual at the International Islamic University of Malaysia (IIUM). Employing a theory of planned behavior model as a baseline theory, a set of questionnaire is constructed to measure donor (waqif) giving intention behavior and data are analyzed accordingly. Concerned with findings, attitude, subjective norm and perceived behavioural control are instrumental in determining cash waqf participation amongst those intellectual. Besides attitude, subjective norm and perceived behavioral control, religiosity is found to have a significant effect on the behavioral intention. Limitations and future researches are outlined.